ALGORITHM OF TAKING DECISION ON PROCEDURE TO BE FOLLOWED IN A BANKRUPTCY CASE - V. N. Alferov (Модернизация, инновация, развитие, 2016)
Choosing the procedure to be followed in a bankruptcy (insolvency) case and analysis of the debtor’s financial condition is one of most important arbitration process stages. It is proposed that the choice of the bankruptcy procedure be made on the basis of comparison between the totalamount of debts according to the creditors’ claims and the income both earned before the bankruptcy proceedings and accumulated in the course of it. Example of calculation of debt amount to be matured resulting from the bankruptcy case procedure is brought about with dueaccount of recent changes in the bankruptcy legislation.